2015
DOI: 10.1542/peds.2015-1945
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Pediatric Burns on the Circulatory System

Abstract: The systemic responses to burns (in particular, elevated levels of catecholamines and stress hormones) have been shown to have an impact on cardiac function for at least 3 years in children with burns. However, it is not clear if these changes lead to long-term effects on the heart. The aim of this study was to assess whether pediatric burn injury is associated with increased long-term hospital use for circulatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…based on differential responsive burn treatments and is the standard classification used in Western Australia Population-based Burn Injury Project studies. 24,33,34 Baseline comorbidity (yes/no) was assessed with a 5-year lookback period 35 using the Charlson comorbidity index 36 and the principal and additional diagnoses data in the hospital morbidity records. Congenital anomaly was identified using principal and additional diagnoses (ICD-10-AM: Q00-G99).…”
Section: Methodsmentioning
confidence: 99%
“…based on differential responsive burn treatments and is the standard classification used in Western Australia Population-based Burn Injury Project studies. 24,33,34 Baseline comorbidity (yes/no) was assessed with a 5-year lookback period 35 using the Charlson comorbidity index 36 and the principal and additional diagnoses data in the hospital morbidity records. Congenital anomaly was identified using principal and additional diagnoses (ICD-10-AM: Q00-G99).…”
Section: Methodsmentioning
confidence: 99%
“…Data by Duke et al suggest that adult and pediatric burn survivors are more prone to sequelae of cardiovascular disease later in life. 8 , 9 However, no prospective studies have followed a cohort of survivors to assess the progression of morphologic and functional changes. Based on data showing systolic and diastolic dysfunction as well as myocardial fibrosis to be independent risk factors for poor cardiovascular and overall health, it is reasonable to assume that, in children surviving burn injury, cardiovascular disease burden may increase disproportionally later in life.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Two recent population-based longitudinal studies were conducted in adults who sustained burn injuries as children or young adults to assess long-term morbidity and mortality due to a variety of cardiovascular diagnoses. 8 , 9 Although the spectrum of cardiovascular diagnoses included in these analyses was broad, the authors reported significant increases in incidence and length of hospitalization as well as mortality related to cardiovascular disease among middle-aged survivors of pediatric burn injury. The importance of this clinical problem may be considerable given that systolic and diastolic dysfunction are powerful predictors of poor cardiovascular prognosis, morbidity, and mortality in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…A long term follow-up study showed that burn injured children had an increased risk of arthritis, fractures, and pulmonary conditions compared to their non-burned peers, even following non-severe burns [ 10 ]. Accordingly, pediatric burn patients had increased hospital admission rates for respiratory infection [ 11 ], cardiovascular diseases [ 12 ], and musculoskeletal diseases [ 13 ], and even an increased risk of mortality in the long-term [ 14 ]. Although the specific causes of those physical and physiological consequences years beyond the burn injury have yet to be identified, lack of physical activity might play a role.…”
Section: Introductionmentioning
confidence: 99%